Discrimination of Seven Anopheles Species from San Pedro de Urabá, Antioquia, Colombia, by Polymerase Chain Reaction–Restriction Fragment Length Polymorphism Analysis of Its Sequences (2007)
ABSTRACT: Accurate identification of anopheline species is essential for vector incrimination and implementation of appropriate control strategies. Several anopheline species are considered important malaria vectors in Colombia; however, species determination is complicated by cryptic morphology and intra-individual variation. We describe polymerase chain reaction–restriction fragment length polymorphism (PCR-RFLP) of internal transcribed spacer 2 (ITS2) sequences for differentiation of seven Anopheles species collected in a locality in Antioquia, Colombia, with high levels of malaria transmission. Each of these seven species can be identified by unique AluI PCR-RFLP restriction patterns. Comparisons of morphologic identification with molecular identification of voucher specimens confirmed species designation for 886 wild-caught anophelines. This new method can be used as a diagnostic tool for discrimination of anopheline species of medical importance in this region, some of which have overlapping morphologic characters and for conducting complementary studies where rapid and accurate identification of large numbers of specimens is needed.